Implementasi Branding 4.0 Berbasis Media Sosial dalam Meningkatkan Citra Sekolah: Penelitian - Robi’atul Adawiyah; Ahmad Thohirin; Suyitno; A. Faizin (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Digital technology is forcing schools to create a brand strategy that can adjust to build a good image and make the community trust them. Branding 4.0, which uses social media, is a strategic method that works well in this situation. This study aims to look at how to design, carry out, and evaluate Branding 4.0 based on social media in order to improve the school's image. The research uses a descriptive qualitative approach with the location being SDN Pandaan I, in Pasuruan Regency. The subjects include the school principal, teachers, teaching staff, and the school's social media administrators. Data was collected through in-depth interviews, observation, and document study. Data analysis was done using the interactive model by Miles and Huberman, and combining sources and techniques to ensure the data is valid. The results show that Branding 4.0 is designed by using social media as the main communication channel for the school, implemented through the regular sharing of content about school activities and achievements, and evaluated based on public responses and levels of trust. Applying Branding 4.0 based on social media helps improve the school's image positively in the eyes of the community.